Parasites in fisheries and mariculture - Timi, Juan Tomas (2015)
Traditionally, parasitology has been concerned with the harmful effects of parasitic organisms; it is basically an applied science. Since its founding in the field of medicine, and later in veterinary medicine, parasitology has been mainly devoted to generating knowledge, which is applicable to parasite control and management, and eventually to their eradication. However, the complexity of parasitism, as revealed over recent decades by workers in various specialisms of parasitology, makes the application of management and control measures very difficult in natural environments. This is particularly true in the marine realm, where however some applied aspects of parasitology, other than those devoted to control and management of parasites, have been shown to be of great importance for fisheries, human health, biological control of introduced species and environmental sciences (Rohde, 2002). The relationship of parasitology with mariculture practices, which are carried out mostly on artificial and controlled systems, follows a more classical approach, focusing on the development of strategies of prevention, management and control of pathogens.